As cidades contemporâneas e suas tecnologias: a perspectiva do City Information Modeling - Jaime, Iasmin de Sousa (2019)
The growth of cities and increasing population have provided several changes to be observed in the planning of cities, a society of few predictable directions is seen, often changing their ways of understanding and giving meaning to things. Coping with this new demand, one can notice the change in the modes of architectural and urbanistic production, in addition to the complex needs of the city. Studies have been carried out to solve these problems, among them, the use of technologies in the context of urban design, planning and management of cities. This paper presents the City Information Modeling (CIM) and other technologies applied in contemporary cities, with the objective of recognizing it as a technology and facilitator of urban management. From the methodological point of view, the research has an exploratory character, with a deep bibliographical revision, aiming to gather the greatest amount of information about the subject and to enable the construction of a conceptual structure to identify the possible applications of a CIM model. It is verified that this discussion is vast and complex, mainly due to the diversity of concepts related to the CIM, there is no unanimity about the concept among the several authors mentioned. The results obtained make it possible to verify that this new paradigm is in constant development, and it can undoubtedly be a tool of extreme relevance for city management, as well as for developers of urban projects. The conceptual framework of the use of CIM models has provided a more systemic view of the process involving the cities and the number of agents involved, such as the great challenge that the CIM has to face. The CIM is an incipient technology, and as City Information Modeling there is still a range of transformations that must occur, especially in public management structures for the operation of the process. To encompass all the complexity of a city in a model will require a long way to go, mainly due to the great political, legal and operational barriers.